SIMON SAYS GAME ON PRACTICING LISTENING SKILL: STUDENTS’ PERSPECTIVES - Anggi Anggraini Nasution (XXXXXXXX, 2022)
This research was aimed to find out students’ perspective of Simon Says game for practicing their listening class. The subject of this research was students on grade VIII junior high school, in 2020 academic year. This research was conducted by using qualitative research. The data used in this research were; questionnaire, interview sheet and photography evidence. The questionnaire in this research consisted of six questions that related to Students’ perspective of Simon Says game for practicing their listening. The researcher distributed questionnaire for twenty five students in grade VIII-3 of MTsS Madinatussalam’s students. The researcher also did interview for some students. The researcher distributed six questions too in interview session to students that still related to students’ perspectives of Simon Says game for practicing their listening. The result of this research showed that almost all students have positive perspectives in Simon says game for practicing their listening. They agree that Simon Says game makes them easier to practice their listening in a fun way. They also agree that Simon says game can make their class atmospheres’ be active. They said they are being attractive while playing this game for listening practice class.  Keywords: Listening; Simon Says game; Students’ Perspective; Listening Practice; Listening Comprehension.